Pengaruh Pendapatan Dan Gaya Hidup Terhadap Minat Investasi Emas Di Kota Bogor - Nada Ilmanna Fiah; Immas Nurhayati; Renea Shinta Aminda (CV. ITTC INDONESIA, 2023)
This study aims to determine whether income and lifestyle factors can influence interest in gold investment in Bogor City. In this study, researchers took a sample of 100 respondents, namely people who live in Bogor City, who have bought gold, both gold bars and gold jewelry. Sampling using purposive sampling technique, data analysis in this study using validity test method, reliability test, classical assumption test, multiple linear regression analysis, t test and f test with the help of SPSS program. The variables in this study are Gold Investment Interest (Y), income (X1), and Lifestyle (X2).The results of this study prove that income has a significant positive effect on gold investment interest in Bogor City, and lifestyle has a significant positive effect on gold investment interest in Bogor City. Keywords: Income, Lifestyle, and Gold Investment Interest.